2013
DOI: 10.1002/jso.23403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic risk factors of tumor recurrence in patients with node-negative early breast cancer after mastectomy

Abstract: LVI and Nottingham grade 3 were the independent risk factors predicting tumor recurrence for patients with NNBC. Adjuvant radiotherapy might be considered in NNBC patients with these unfavorable factors to improve the RFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…In node-negative patients, several studies showed LVI was prognostically important because patients with positive LVI had a higher rate of distant metastases and higher local recurrence rate after breast conservation therapy [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In node-negative patients, several studies showed LVI was prognostically important because patients with positive LVI had a higher rate of distant metastases and higher local recurrence rate after breast conservation therapy [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…15,2327 When LVI was absent, the risk of any nodal involvement was 0.28 (95% CI, 0.26–0.31) compared to when it was present. Additionally, LVI is well documented to be a risk factor for local recurrence after both BCT and mastectomy 2830 , raising the possibility that an increased frequency of LVI could be responsible for the higher rates of local recurrence in the breast and chest wall seen with TN breast cancer. However, we found that of all the subtypes, TN cancers were least likely to have LVI.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a small proportion of patients fail locoregionally in the modern treatment system. A few trials have demonstrated that subgroups of pT1-2N0 patients with multiple adverse risk factors were at higher risk of LRR [ 9 , 11 , 12 , 18 21 ]. Although the risk factors which were associated with LRR have varied among different studies and time eras, the proportion of patients at high risk of LRR was usually around 5–15%.…”
Section: Discussionmentioning
confidence: 99%